Solving of organizational and legal problems of Kazakh-Chinese trade-economic cooperation - Shyaujian , Zhi; Sarsembayev, M.A. (Bulletin of the Karaganda University “Law Series”, 2024)
China, along with Russia, is the largest trading partner of the Republic of Kazakhstan. Kazakhstan’s trade and economic relations are based on a solid international legal framework of bilateral trade and economic treaties and agreements. Nevertheless, the parties are striving to further accelerate these relations, which could quickly bring more substantial dividends. In this regard, the parties, based on such interest, show interest in the problems that have arisen and are emerging in the process of Kazakh-Chinese bilateral trade, which need to be resolved at an accelerated pace. This article is largely devoted to the formulation of recommendations and proposals, the implementation of which will bring much more success in this important area of cooperation between Kazakhstan and China. In the light of the problems in the Red Sea and global trade shipping, including with regard to China, Kazakhstan proposes to use its territory and the territories of other countries to the maximum as a trade transit of goods from China to Europe. This will benefit China (saving time in the delivery of goods), Kazakhstan and other countries - transit dividends, European countries - prompt delivery of goods, affordable prices for these goods.